2020
DOI: 10.1590/1981-6723.17919
|View full text |Cite
|
Sign up to set email alerts
|

Hygienic-sanitary quality and effect of freezing time and temperature on total antioxidant capacity of human milk

Abstract: Knowledge of the hygienic-sanitary quality of raw human milk helps to establish the best storage conditions for the preservation of its nutritional and functional components. Therefore, this study aimed to evaluate the hygienic-sanitary quality of human milk extracted at the mothers’ homes, and to analyze the effect of freezing time and temperature on the milk’s total antioxidant capacity. Milk of five mothers was evaluated individually for Staphylococcus aureus, total aerobic mesophilic counts, mold and yeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…There was variation in the antioxidant profile until the 21 st day at both temperatures (4 °C and -20 °C). However, Lopes et al (2020) observed a change in the antioxidant profile when the human milk was stored at temperatures lower than -40 ºC, demonstrating that freezing may not be the best way to store human milk.…”
Section: Discussionmentioning
confidence: 97%
“…There was variation in the antioxidant profile until the 21 st day at both temperatures (4 °C and -20 °C). However, Lopes et al (2020) observed a change in the antioxidant profile when the human milk was stored at temperatures lower than -40 ºC, demonstrating that freezing may not be the best way to store human milk.…”
Section: Discussionmentioning
confidence: 97%